Mechanism of mechanical strength degradation and microstructure evolution of anthracite induced by supercritical carbon dioxide - Yichao JIA; Dong YANG; Xudong HUANG; Dingwei SUN; Liguo HE (Meitan kexue jishu)
In order to reveal the effect of supercritical carbon dioxide on the mechanical strength and microstructure of anthracite in the process of CO2 injection into deep coal seams, takes anthracite as the research object, the degradation characteristics of coal by supercritical carbon dioxide under two constant temperatures (40 ℃ and 60 ℃) were investigated. The self-developed supercritical carbon dioxide immersion equipment combined with coal uniaxial loading device was used to preliminarily determine its mechanical strength. The structures such as pores and cracks were characterized by CT scanning system, and the physicochemical effects of different soaking days (0, 1, 3, 5, 7 d) on pores and cracks were analyzed. The intrinsic relationship between macroscopic strength loss and microstructure evolution of anthracite after supercritical carbon dioxide immersion was revealed. The results show that supercritical carbon dioxide has a certain time effect on the deterioration of the macroscopic strength of anthracite. With the increase of soaking time, the deterioration effect gradually weakens and gradually reaches a certain value. The main period of the deterioration is within 0−5 days of soaking, and the average size of the damaged particles gradually increases with the change of failure mode. Compared with the constant temperature of 60 ℃, the supercritical carbon dioxide under constant temperature of 40 ℃ has a more obvious degradation effect on coal. With the help of CT scanning system, it was found that after the supercritical carbon dioxide immersion, the white minerals disappeared, the “solution holes” gradually expanded, the cracks in the new holes continued to develop, and the crack opening increased. The internal pore and fissure of the coal sample developed rapidly into a relatively continuous pore group within 0−5 days, and then the internal pore and fissure developed slowly and gradually became stable. The supercritical carbon dioxide intrudes into the coal, and by extracting organic matter in the coal matrix and dissolution of carbonate mineral components, it forms “dissolution pores”, destroys the crystal structure, and leads to the gradual development of internal pore groups. With the increase of specific surface area, the adsorption capacity of coal increases, and the“swelling effect”further increases the development of pore and fracture, and finally leads to the change of macroscopic mechanical strength. According to the analysis of the macroscopic strength loss mathematical model, after the coal is soaked in supercritical CO2, the strength envelope shifts to the right, the molar stress circle shifts to the left, and the internal friction Angle and cohesion become smaller, resulting in the macroscopic strength loss of the coal.